Influence of binders on physical properties of fuel briquettes produced from cassava rhizome waste. (2016) - Sen, Ranjit; Wiwatpanyaporn, Sujinda; Annachhatre, Ajit Padmakar
Investigations were undertaken to produce fuel briquettes from cassava rhizome waste with five binders namely molasses, starch gel, concentrated slop, cassava pulp and soybean residue at the ratios of 6:4, 7:3, 8:2, 9:1 and 10:0. Physical properties viz. density, compressive strength and impact resistance index of briquettes showed gradual improvement with the increased amount of binders. Briquettes produced from cassava rhizome charcoal with molasses, starch gel and concentrated slop as binders in proportion of 6:4 and 7:3 yielded higher density ranging from 0.69 to 0.91 g cm −3, compressive strength from 8.51 to 14.94 kg cm −2, impact resistance index from 153.7 to 416.7 and calorific values from 21, 670 to 24, 367 KJ kg −1, respectively. From economic analysis, it was found that briquettes produced from cassava rhizome charcoal with either molasses or starch gel binder in proportion of 7:3 were found best with highest BCR of 2.01 and 2.15, respectively.